2019
DOI: 10.1123/jsm.2018-0101
|View full text |Cite
|
Sign up to set email alerts
|

Inducing Destination Images Among International Audiences: The Differing Effects of Promoting Sport Events on the Destination Image of a City Around the World

Abstract: The purpose of this study is to examine how effective the international promotion of a sport event is on changing the destination image prior to the event if the sport event lacks global popularity. The authors conducted a quasi-experimental posttest research design, in which they used promotional information of a Tour de France stage to manipulate the destination image nonvisitors (N = 3,505) from nine different nations have of the hosting city, 5 months prior to the actual event. Results show that treating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 44 publications
(55 reference statements)
0
10
0
1
Order By: Relevance
“…Audience. The audience at a sport event can range from exclusively local residents or communities to global audiences (Heere et al, 2019). In general, local sport events attract a predominantly local audience, while major and mega sport events extend to regional, national and even global audiences.…”
Section: Sport Logistics Researchmentioning
confidence: 99%
“…Audience. The audience at a sport event can range from exclusively local residents or communities to global audiences (Heere et al, 2019). In general, local sport events attract a predominantly local audience, while major and mega sport events extend to regional, national and even global audiences.…”
Section: Sport Logistics Researchmentioning
confidence: 99%
“…In fact, ineffective partnerships among private and public entities acted as a bottleneck towards effective collaboration to take advantage of sport events in destination branding. Moreover, Heere et al (2019) stated that the effect of events was different from country to country, pending on the popularity of the event or sport in the specific nation, and whether the nation itself offered similar events.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, residents' quality of life may be directly impacted by the event, be it positive or negative, before, during, and/or after the event. Research has demonstrated that hosting one-off major sporting events generally results in negative ecological impacts [3], as well as a lack of substantial economic impact [4][5][6][7] and sustainable tourism impact [8]. This has shifted the justification for hosting mega-events towards trying to demonstrate positive benefits from other features of events such as urban planning [9], or less tangible features such as social impacts [10] and sport participation impacts [11] affecting local communities and residents after the event has taken place.…”
Section: Introductionmentioning
confidence: 99%